Beskyttelse af Landbrugsbygninger mod Lynilden. Foredrag, d. 21. Febr. 1894. - Appel, Jacob (Tidsskrift for Landøkonomi, 2018)
Beskyttelse af Landbrugsbygninger mod Lynilden. Foredrag, d. 21. Febr. 1894.